Benzotriazole as an electrolyte additive on lithium-ion batteries performance - Hamenu, Louis; Madzvamuse, Alfred; Mohammed, Latifatu; Lee, Yong Min; Ko, Jang Myoun; Bon, Chris Yeajoon; Kim, Sang Jun; Cho, Won Il; Baek, Yong Gu; Park, Jongwook (한국공업화학회, 2017)
Liquid electrolyte consisting of 1 M LiPF6 in ethylene carbonate (EC)/dimethyl carbonate (DMC) and 0.1 wt% benzotriazole (BzTz) is studied in LiCoO2//graphite battery system at room temperature. Benzotriazole addition introduces excellent electrochemical stability (5.6 V vs Li) and good ionic conductivity properties at room temperature. Also, this electrolyte shows good cycling performance and better discharge capacities at high C-rates relative to the pristine electrolyte. Furthermore, the additive allows the formation of a good solid electrolyte interphase (SEI) per cyclic voltammetry (CV) examination. These specialized properties make this liquid electrolyte ideal for high power and high voltage applications. (C) 2017 The Korean Society of Industrial and Engineering Chemistry. Published by Elsevier B.V. All rights reserved.